Family and adolescence - Navarrete Aguilar, Alejandro (2001)
Therapist must encourage creativity and help families to form their standards for living together and not so much searching the ideal. Today families have had changes in their structure in comparison to the families of previous decades. It is important for parents to understand the adolescent culture.